Dietary intake in high-level swimmers. A 32-week prospective cohort study - Karina Romeu Montenegro; Bruno Manfredini Baroni; Cláudia Dornelles Schneider; Cássia Daniele Zaleski Trindade; Flávio Antônio de Souza Castro (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS To determine whether high-level swimmers present adequate energy and macronutrient intake during each training phase of the season. METHODS A 32-week prospective cohort study was conducted with 18 elite swimmers (10 men, 20±2 years; 8 women, 20±3 years) from a competitive swimming club. This period comprised two training macrocycles, each one divided in four training phases: general, mixed, specific and competition. Dietary intake, estimated energy expenditure and daily energy requirements were assessed in every training phase. Body composition was evaluated five times throughout the season. Energy and macronutrient consumption were compared with the energy expenditure and the literature recommendations, respectively. RESULTS Athletes maintained a relatively constant dietary intake throughout the season, regardless the different needs of each training phase. The balance between energy consumption and expenditure was negative in all training phases (p=0.02; d between 1.5-6.2) for women, while men did so in half of phases (p<0.01; d between 0.3-4.1). Swimmers had higher protein intake than recommendations in 73% of the evaluations, while carbohydrate and lipids intake were lower than recommendations in 76% and 69% of the evaluations, respectively. CONCLUSION Athletes did not meet the energy demands and specific macronutrient requirements of each training phase of the competitive season.